(untitled) (Swiss Medical Weekly, 2021)
We report the occurrence of immune thrombocytopenia (ITP) in a 77-year-old man a few days after receiving the first dose of the COVID-19 mRNA vaccine tozinameran (Comirnaty®). The patient was treated with systemic corticosteroids, intravenous immunoglobulins and eltrombopag. He elected to proceed with the second dose of tozinameran 14 weeks after the first and his platelet count remained stable under a tapered eltrombopag dose. To our knowledge, this is the first case in which a second tozinameran dose has been administered to a patient who developed presumed secondary ITP after the first vaccination. We also report global pharmacovigilance data for the occurrence of ITP after vaccination with tozinameran.